Matrix metalloproteinase system in blood serum in patients with squamous cell head and neck carcinomas - Ye. V. Klisho; I. V. Kondakova; Ye. L. Choynzonov; O. V. Cheremisina; D. A. Shishkin (Бюллетень сибирской медицины)
The concentrations of matrix metalloproteinases (MMP-2, -3, -9) and their tissue inhibitors (TIMP-1, -2) were studied in blood serum of 193 patients with squamous cell head and neck carcinoma (SCHNC) and in 38 healthy donors using immunoenzymatic assay. The decreased MMP-3 and TIMP-1, -2 levels were found in patients with oral cavity tumors as compared to patients with laryngeal cancer. The serum MMP-9 and TIMP-1 levels were significantly higher in head and neck cancer patients than in healthy subjects. High TIMP-1 and MMP-9 levels in blood serum of patients with SCHNC should be greatly attended for detection of their predictive and prognostic significances.